Perilaku Konsumen: Utility Versus Maṣlaḥah sebagai Rasionalitas dalam Ekonomi Islam - Fadllan, Fadllan; Lailatul Maufiroh (El-Qist: Journal of Islamic Economics and Business (JIEB), 2024)
This study explores the conceptual distinction between utility and Maṣlaḥah as competing foundations of consumer rationality within Islamic economics. Through an extensive library-based analysis of classical and contemporary literature, the research investigates whether consumption is driven by needs (ḥājah) or desires (raghbah), and how these motivations align with the objectives of conventional versus Islamic economic systems. Findings reveal that while utility emphasizes subjective satisfaction based on individual preferences, Maṣlaḥah offers a more objective, ethical, and purpose-driven approach grounded in the maqāṣid al-sharīʿah. The study highlights that Maṣlaḥah-oriented consumption incorporates both material benefit and spiritual blessing, thus promoting social welfare and moral responsibility beyond individualistic gain. This contrast underscores the epistemological divergence between Islamic and neoclassical economic paradigms in conceptualizing rational behavior. The specific contribution of this study to the international research field lies in its critical reevaluation of rationality in consumer behavior by integrating the normative framework of Maṣlaḥah as an alternative to utilitarianism. It contributes to global scholarship by advancing Islamic economics beyond jurisprudential foundations into behavioral and philosophical dimensions, enriching comparative discourse in economic theory, ethics, and public policy. The research encourages rethinking consumption beyond mere satisfaction, offering a holistic model that integrates ethics, social justice, and sustainable well-being.